Footloose a Paramount release presented with MTV Films, Spyglass Entertainment of a Dylan Sellers, Zadan/Meron, Weston Pictures production ; produced by Craig Zadan, Neil Meron, Sellers, and Brad Weston ; directed by Craig Brewer ; screenplay, Dean Pitchford and Craig Brewer. - Brewer, Craig; Wormald, Kenny; Hough, Julianne, 1988-; Quaid, Dennis; Lurie, Deborah (Hollywood, Calif. : Paramount, 2012)
City boy Ren McCormick moves to a Southern town where dancing has been banned and encourages his friends to fight for the right to dance.
Remake of the 1984 film of the same name directed by Herbert Ross.
Originally released as a motion picture in 2011.
Features: commentary by director Craig Brewer, additional scenes, deleted scenes with optional commentary by director Craig Brewer, "Fake ID" music video by Big & Rich, UltraViolet enabled.
Camera, Amelia Vincent ; editor, Billy Fox ; production designer, Jon Gary Steele ; choreographer, Jamal Sims ; music, Deborah Lurie.
Kenny Wormald, Julianne Hough, Dennis Quaid, Andie MacDowell, Miles Teller, Patrick John Flueger, Ziah Colon, Ray McKinnon.
MPAA rating: PG-13.
Keywords: Teenagers and adults -- Drama; Dance -- Drama; Music -- Drama; Small cities -- Drama; Fathers and daughters -- Drama; Film remakes; Video recordings for the hearing impaired; Fiction films; Coming of age films; Feature films